The end of the European era, 1890 to the present - Felix Gilbert (W. W. Norton, 1991)
The book takes full account of the momentous events of 1989-1990 in Eastern Europe. It traces the collapse of Communist party rule in Poland, Hungary, East Germany, Czechoslovakia, Bulgaria, and Rumania, as well as the struggle for reform within the Soviet Union. A vivid narrative conveys the drama of the Berlin Wall's collapse, the surprising sucess of ceaucescu. The book assesses the significance of Gorbachev's reforms, Germany's reunification, and international realignments against the backdrop of Europe's tumultuous history in this century. The book also focuses on Western Europe through the end of the 1980s, paticularly on new directions in domestic politics, foreign relations, and progress toward a single European market 1992